Minor attraction: a queer criminological issue - Walker, Allyson (Critical criminology, 2017)
Despite a cultural tendency to sexualize youth, individuals who are primarily attracted to minors are subject to suspicion and stigma across society, extending into criminology and criminal justice. The prevailing assumption is that minor-attracted persons (MAPs) are mentally ill and predatory. However, there exists evidence that minor attraction is a sexual orientation, and the parallels between the treatment of MAPs and LGBT populations are striking. Employing queer criminology’s use of deconstructionist techniques, we address the current state of criminology and criminal justice, which sees MAPs as a suspect population warranting formal control. We then argue for the use of queer criminology as a framework for future research with minor-attracted populations, which could have important implications for criminal justice practice and policy.